- Determinants of Obligating Un obligatory in Al-Maari’s Poetry - محمد نايف ابتسام (Journal of College of Education, 2021)
This research seeks to read the necessity of what is not necessary in the poetry of Abi Al-Ala ’Al-Maari concerned with three topics, the first of which is: in the term and its concept, and the second: in the rhythmic directives of the necessities, and the third: in the graphic directives, whereas the justification for this is that Abu Al-Al-Maari singled out the requirements for an independent poetic poetry. And he worked on creating weights or cuts, adhering to the restrictions imposed by the term on him, and therefore the first wave was rhythmic. As the last thing on the sentence stands in the poetic house, the photogrammetric orientation becomes an observed issue from the reading field, and the research has singled out the rhythmic and photorealistic mentors of the applied area in this research from this point, as it contributes to enriching the rhythmic and graphic components clearly, and they are in the necessities more The routers make a difference.